Unusual Presentation of a Rare Tumor of the Dorsal Surface of the Foot. (22nd March 2011) - Hocar, O.; Yacoubi, H.; Akhdari, N.; Amal, S.; Ait Essi, F.; Latifi, M.; Rais, H.; Belaabidia, B.
Abstract : Calcifying aponeurotic fibroma (CAF) was originally described by Keasbey in 1953 as juvenile aponeurotic fibroma, most commonly occurring in the palms of the hands and soles of the feet in children and adolescents. It usually presents as a firm, painless mass without preceding trauma. We report a case of this rare condition with an unusual presentation in a 60-year-old woman affecting the dorsal surface of the foot. It is a relatively benign condition with a good prognosis following complete surgical excision. It may have a slightly increased incidence in males. The accurate diagnosis is based only on histology but it is essential to differentiate it from other sinister lesions such as fibrosarcoma that may lead to amputation.